2019
DOI: 10.4067/s0719-38902019005000505
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia in Vitro De Extractos Del Hongo Comestible Pleurotus Ostreatus Kumm Para El Control De Sitophilus Zeamais Motschulsky

Abstract: El gorgojo del maíz, Sitophilus zeamais Motschulsky, es a nivel mundial una de las plagas más importantes de los cereales almacenados. Actualmente su manejo se realiza principalmente con insecticidas sintéticos, con escasa variación de mecanismos de acción, por lo que una alternativa son los compuestos naturales, especialmente los extractos vegetales. El objetivo de esta investigación fue evaluar, en condiciones de laboratorio, el efecto insecticida/insectistático de extractos de Pleurotus ostreatus Kumm con s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
2
4
2
Order By: Relevance
“…The concentrations of 50, 100, and 200 mL extract L -1 solvent exceeded 80% of germinated seeds, and the treatment using 300 mL extract L -1 solvent was the one with the best results, reaching 97.5% germination. Our germination values are higher than those of Pino et al (2019), who used extracts in ethyl acetate, hexane, and methanol, achieving germination values lower than 50%. Treatments higher than 100 mL extract L -1 solvent of the hydroalcoholic extract of P. ostreatus do not affect maize germination due to the concentration of ethanol absorbed 2 Slope value ± standard error.…”
Section: Table 1 Repellency Index (Ri) Of An Hydroalcoholic Extracts ...contrasting
confidence: 71%
See 4 more Smart Citations
“…The concentrations of 50, 100, and 200 mL extract L -1 solvent exceeded 80% of germinated seeds, and the treatment using 300 mL extract L -1 solvent was the one with the best results, reaching 97.5% germination. Our germination values are higher than those of Pino et al (2019), who used extracts in ethyl acetate, hexane, and methanol, achieving germination values lower than 50%. Treatments higher than 100 mL extract L -1 solvent of the hydroalcoholic extract of P. ostreatus do not affect maize germination due to the concentration of ethanol absorbed 2 Slope value ± standard error.…”
Section: Table 1 Repellency Index (Ri) Of An Hydroalcoholic Extracts ...contrasting
confidence: 71%
“…The results of repellency tests recorded RI values greater than 1, which according to Mazzoneto and Vendramim ( 2003) means no repellent effect on adults of S. zeamais (Table 1). Results do not agree with Pino et al (2019), who assessed extracts of P. ostreatus in ethyl acetate, distilled water, methanol, and hexane at concentrations of 0.5%, 1.0%, 2.0%, and 4.0% against adults of S. zeamais. Specifically, the treatments with ethyl acetate at the concentration of 1.0% presented, according to the criteria of Bustos et al (2017), a very high repellency, while the extract with distilled water showed weak repellency.…”
Section: Repellent Effectcontrasting
confidence: 66%
See 3 more Smart Citations